The Difference of Airway Irritative Effect of Halotane and Isoflurane as Inhalational Anestethic - Whendi Setyawan; Marthunus Judin; Bhisma Murti (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2012)
Background:Isoflurane and halothane have been used broadly. Airway irritation is one of the side effect from both isoflurane and halothane and have fairly important clinical implication in the provision of both anestethic agent. Methods:The Research is observational analitic research. The population of the research was the patient completed surgery with general anesteshia in IBS(InstalasiBedahSentral) RSUD dr. Moewardi, Surakarta and was transferred to the ward. The data of odynophagia and the incidence of chough were analyzed using Chi Square method. Results:This quote sampling research uses 30 samples divided into two groups, 15 peoples get Isoflurane as their anestethic agent, the other 15 get Halothane. The results of all samples obtained from both groups experienced a sense of hoarseness in the throat. Data incidence of odynophagia obtained that 15 patients of isoflurane experienced odynophagia and 7 patients found in the halothane. Data incidence of chough obtained that 7 patients of isoflurane experienced chough and none of the halothane patient experienced chough. Analitical result on the incidence of odynophagia obtained that patients given isoflurane are at risk for odynophagia 35.13 times greater than halothane, and the increased risk was statistically significant (OR: 35.13, 95% CI 1.78 to 693.30, p = 0.002) and the results cough incidence analysis, found patients given isoflurane are at risk for experiencing cough 27.35 times greater than halothane, and the increased risk was statistically significant (OR: 27.35, 95% CI 1:36 to 539.7, p = 0.004). Conclusions:The conclusions of this study isisoflurane has the effect of irritating the respiratory tract is greater than halothane as inhaled anesthetic. Isoflurane itself can still be used in elective surgery such as halothane when accompanied by adequate premedication Keywords:Isoflurane-Halothane-Iritation-Airway.